so sánh A = 10 mũ 10 + 1 / 10 mũ 11 + 1 và B = 10 mũ 9 + 1 / 10 mũ 10 + 1 AI LÀM ĐC TÔI KHEN TÀI

so sánh
A = 10 mũ 10 + 1 / 10 mũ 11 + 1 và B = 10 mũ 9 + 1 / 10 mũ 10 + 1
AI LÀM ĐC TÔI KHEN TÀI

2 bình luận về “so sánh A = 10 mũ 10 + 1 / 10 mũ 11 + 1 và B = 10 mũ 9 + 1 / 10 mũ 10 + 1 AI LÀM ĐC TÔI KHEN TÀI”

  1. Ta có:
                  A=[10^10+1]/[10^11+1]
    =>10A=[10^11+10]/[10^11+1]
                    =[10^11+1+9]/[10^11+1]
                    =1+[9]/[10^11+1]
                B=[10^9+1]/[10^10+1]
    =>10B=[10^10+10]/[10^10+1]
                   =[10^10+1+9]/[10^10+1]
                   =1+[9]/[10^10+1]
    Vì 10^11>10^10
    =>10^11+1>10^10+1
    =>1/[10^11+1]<1/[10^10+1]
    =>9/[10^11+1]<9/[10^10+1]
    =>1+9/[10^11+1]<1+9/[10^10+1]
    Nên 10A<10B
    =>A<B
    Vậy A<B

    Trả lời
  2. Ta có:
    10A=[10.(10^10+1)]/[10^11+1]
    =>10A=[10^11+10]/[10^11+1]
    =>10A=[10^11+1+9]/[10^11+1]
    =>10A=1+[9]/[10^11+1]
    10B=[10.(10^9+1)]/[10^10+1]
    =>10B=[10^10+10]/[10^10+1]
    =>10B=[10^10+1+9]/[10^10+1]
    =>10B=1+[9]/[10^10+1]
    Vì 10^11+1 > 10^10+1 nên [9]/[10^11+1] < [9]/[10^10+1]
    =>1+[9]/[10^11+1] < 1+[9]/[10^11+1]
    =>10A < 10B
    =>A < B
    Vậy A < B

    Trả lời

Viết một bình luận

Câu hỏi mới